놀이치료자의 역기능적 완벽주의와 역전이 관리능력에 따른 군집별 역기능적 완벽주의, 역전이 관리능력, 심리적 소진의 차이 - 오신예; Oh Shin-yae; 이영애; Lee Young-ae (한국놀이치료학회지(놀이치료연구), 2022)
본 연구에서는 놀이치료자의 역기능적 완벽주의와 역전이 관리능력 수준에 따라 군집을 분류한 후, 각 군집유형에 따라 심리적 소진의 차이를 검증하였다. 연구대상은 수도권 지역에서 근무하는 놀이치료자 196명이었으며, 역기능적 완벽주의 척도(PQ), 역전이 관리능력 척도(CFI), 심리적 소진 척도(MBI)를 사용하여 설문조사를 실시하였다. 본 연구를 통해 도출된 결과를 요약하면 다음과 같다. 첫째, 연구 변인 간의 상관분석을 실시한 결과 놀이치료자의 역기능적 완벽주의와 역전이 관리능력은 각각 심리적 소진 간에 유의한 상관이 있는 것으로 확인되었다. 둘째, 놀이치료자의 역기능적 완벽주의와 역전이 관리능력의 수준에 따라 군집을 분석한 결과 4개의 군집이 분류되었다. 셋째, 놀이치료자의 역기능적 완벽주의와 역전이 관리능력의 하위요인에 따라 분류한 군집간에 역기능적 완벽주의, 역전이 관리능력, 심리적 소진의 차이를 검증하였다. 본 연구는 놀이치료자의 성격 변인인 역기능적 완벽주의와 역량변인인 역전이 관리능력이 심리적 소진의 하위요인에 미치는 영향을 동시적으로 탐색하여 소진에 영향을 미치는 요인들을 깊이 있게 분석하였다는 것에 의의가 있다. The purpose of this study is to verify the Differences in Play Therapists’ Dysfunctional Perfectionism, Countertransference Management Ability and Psychological Burnout in terms of cluster-based Dysfunctional Perfectionism and Countertransference Management Ability. The study’s subjects comprised 196 play therapists. The subjects responded to three standardized surveys : Perfectionism Questionnaire (PQ), Counter-transference Factors Inventory (CFI), and the Maslach Burnout Inventory (MBI). The results found in this study are as follows. First, there was a significant correlation in major variables in terms of play therapist’s dysfunctional perfectionism, countertransference management ability and psychological burnout. Second, from our data, four clusters emerged each characterized by a particular the level of dysfunctional perfectionism and countertransference management ability. Third, the data analysis verified the existence of differences in the clusters’ major variables level classified, once again, by dysfunctional perfectionism and subvariant of countertransference management ability. As a result, the data showed a significant differences in Dysfunctional Perfectionism, Countertransference Management Ability and Psychological Burnout levels.